Exploring the detrimental effects of microplastics on Asian seabass (Lates calcarifer) fingerlings survival and health - Suleiman, Saadu Bala; Esa, Yuzine; Aziz, Dania; Ani Azaman, Siti Nor; Hassan, Nadiatul Hafiza; Syukri, Fadhil (Elsevier, 2024)
Microplastics (MPs) are widely used and disposed of indiscriminately, posing a potential threat to aquatic life. Herein, Asian seabass (Lates calcarifer) fingerlings were exposed to various concentrations (1, 10 and 100 ppt or g/kg) of dietary polyethylene MPs for 16 days. The results indicated a significant increase in mortality among the fish fed with dietary MPs compared to the control. Furthermore, histological analysis of the liver revealed moderate-to-severe morphological alterations, hepatocyte necrosis and vacuolisation as the concentration gradient of MPs increased. The severity of the alterations was highest at a concentration of 100 ppt, indicating a direct correlation between MP and liver damage. In addition, RNA sequencing and Gene Ontology term enrichment analysis revealed that a total of 4137 genes were significantly differentially expressed, with 1958 upregulated and 2179 downregulated genes. The significantly enriched terms included ‘oxidoreductase activity’, ‘endocytosis’, ‘mitochondrial’, ‘immune system process’ and ‘lipid catabolic process’. Moreover, the Kyoto Encyclopaedia of Genes and Genomes enrichment analysis demonstrated that dietary MPs triggered oxidative stress, immune response and adaptive mechanism pathways in fish. Thus, MPs can induce metabolic disorders in L. calcarifer, highlighting their potential threat to aquatic organisms.